A CHANGE OF ELECTRIC PROPERTIES OF SEED IS UNDER ACT OF HIGH-FREQUENCY ELECTROMAGNETIC IRRADIATION - Петровський, О. М. (Scientific Progress & Innovations, 2014)
The questions of stimulation of seed before sowing are considered by the high-frequency electromagnetic field considered. The method of irradiation of seed and determination of him is offered electric descriptions. On the basis of structure of cages electric properties of biological fabric which seed consist of are certain. The change of constituents of active resistance is shown depending on frequency of current. It is experimentally proved that it is impossible to erect an equivalent electric chart to the simple cases of connection of resistances and capacities, namely seed can not be considered a neutral dielectric. The method of estimation of intensity of exchange processes is developed depending on electric resistance of seed.